The Positive Impact of Rebranding to Increasing Consumer loyality with Brand Image as the Mediating Variable - Prayoga, Andre; Suseno, Eko (International Journal of Social Science and Business, 2020)
This study aims to analyze the effect of rebranding to consumer loyality with brand image as mediating variable. This research is using quantitative approach. 100 people of Gojek users are the sample, which were chosen with purposive sampling method. Data in this research were collected using questionnaire in Google Form as the instrument, then the data were analyzed using simple regression and Sobel test with the help of IBM SPSS Statistics application. The result shows that rebranding has positive effect fo consumer loyality; brand image has positive effect to consumer loyality; rebranding has positive effect to brand image. Besides, Sobel test result shows that the value of t-count < t-table (1.248 < 1.984), so it can be concluded that brand image does not mediating the rebranding effect to consumer loyality for the Gojek users. The result of this research can be used as a suggestion for the marketings (especially for marketing or a company that is willing to do logo rebranding) to see how the effect of rebranding is to consumer loyality with brand image as the mediating variable.